Human Rights and War Through Civilian Eyes. - Smith, Thomas W. (Pennsylvania studies in human rights., 2016)
Human Rights and War shows how even combatants who profess to follow the laws of war often engage in appalling violence and brutality, ruining economies, rending social fabrics, and collapsing public infrastructure, making clear the limits of international humanitarian law and how it must incorporate human rights perspectives.